Tracing The Role Of Datu Tunggang Parangan In Sowing Islam In Kutai Land - Rahmat Surya; Wijaya, Ida Suryani; Siti Syahar Inayah; A Rivai Beta (PT ARRUS Intelektual Indonesia, 2025)
Abstract: This study aims to describe the role of Datu Tunggang Parangan in the spread of Islam in Kutai Kartanegara Regency. The research uses historical and literature-based methods, with Habib Hasyim bin Musyaiyakh (Datu Tunggang Parangan) as the main subject, and the cemetery caretakers, religious leaders, and community figures as supporting subjects. Primary data were obtained through interviews, while secondary data were gathered from literature sources. The data analysis technique employed is the Miles and Huberman model. The findings of this study reveal that Datu Tunggang Parangan played a significant role in spreading Islam in Kutai Kartanegara by converting King Aji Mahkota along with his family and royal officials to Islam. He then guided and taught Islamic values within the royal court. This process led to many changes in regulations that incorporated Islamic elements and influenced the adaptation of local culture—such as the traditional Erau ceremony, which originally had Hindu characteristics, to become more Islamic in nature. Datu Tunggang Parangan’s close relationship with the royal family was a strategic key in expanding Islamic preaching throughout the Kutai Kartanegara kingdom and played a major role in the broader acceptance of Islam among the local community.